IMPROVING PUBLIC HEALTH THROUGH EARLY DETECTION OF NUTRITIONAL STATUS AND UTILIZATION OF LOCAL FOOD IN MASANGAN KULON SIDOARJO - Hariyani Putri, Pratiwi; Nuriannisa, Farah; Nurmalya Kardina, Rizki; Linda Mutiarani, Anugrah; Wulandari, Catur; Ardany, Silfa; Cony Safarita, Friska; Umi Fauziah, Anisa; Tania Meyhana, Salma; Putri Setyawan, Pramudtya; Dwi Wulansari, Adinda (Community Service Journal of Indonesia, 2025)
Nutritional problems in Indonesia among others undernutrition, overweight/obesity, and non-communicable diseases that can occur across all age groups. Masangan Kulon Village, Sukodono District, Sidoarjo Regency, faces similar challenges with suboptimal utilization of local food resources. Therefore, there is a need for early detection programs for nutritional status and education on the use of local food ingredients for adolescents, adults, and the elderly. Activities were conducted on June 19, 2025, for adults (32 people) and the elderly (22 people), and on July 17, 2025, for adolescents (83 people). Examinations included anthropometry, blood pressure, blood sugar, and nutrition education, accompanied by cooking demonstrations featuring catfish tekwan and corn pudding. The results indicated a variety of nutritional statuses, including central obesity, hypertension, and pre-diabetes in several participants. This program improved nutrition knowledge, skills in processing local foods, and awareness of the importance of preventing non-communicable diseases. The activity has the potential to become an intervention model.